Shear velocity structure beneath the central United States: implications for the origin of the Illinois Basin and intraplate seismicity. (20th March 2016) - Chen, Chen; Gilbert, Hersh; Andronicos, Christopher; Hamburger, Michael W.; Larson, Timothy; Marshak, Stephen; Pavlis, Gary L.; Yang, Xiaotao
Abstract: We present new estimates of lithospheric shear velocities for the intraplate seismic zones and the Illinois Basin in the U.S. midcontinent by analyzing teleseismic Rayleigh waves. We find that relatively high crustal shear velocities ( VS ) characterize the southern Illinois Basin, while relatively low crustal velocities characterize the middle and lower crust of the central and northern Illinois Basin. The observed high crustal velocities may correspond to high‐density mafic intrusions emplaced into the crust during the development of the Reelfoot Rift, which may have contributed to the subsidence of the Illinois Basin. The low crustal VS beneath the central and northern basin follow the La Salle deformation belt. We also observe relatively low velocities in the mantle beneath the New Madrid seismic zone where VS decreases by about 7% compared to those outside of the rift. The low VS in the upper mantle also extends beneath the Wabash Valley and Ste. Genevieve seismic zones. Testing expected VS reductions based on plausible thermal heterogeneities for the midcontinent indicates that the 7% velocity reduction would not result from elevated temperatures alone. Instead this scale of anomaly requires a contribution from some combination of increased iron and water content. Both rifting and interaction with a mantle plume could introduce these compositional heterogeneities. Similar orientations for the NE‐SW low‐velocity zone and the Reelfoot Rift suggest a rift origin to the reduced velocities. The low VS upper mantle represents a weak region and the intraplate seismic zones would correspond to concentrated crustal deformation above weak mantle. Key Points: Vs structure beneath the central U.S. is measured by analyzing Rayleigh wave phase velocities The Reelfoot Rift has influenced the Illinois Basin geometry and intraplate seismicity Low mantle velocities beneath the failed rift appear to result from rifting driven refertilization